Regulation of the Role of Mediators in Efforts to Resolve Employment Disputes: A Comparative Study of Indonesia and United Kingdom - Hasnan Hasbi; Dea Larissa (Manunggal Halim Jaya, 2024)
This study aims to examine the regulatory frameworks for mediators in employment dispute resolution in Indonesia and the United Kingdom. The research method involves a comparative analysis of the two countries' approaches to regulating the mediation process, mediator qualifications, and the enforceability of mediated agreements. The findings of the study indicate that a robust regulatory environment is crucial in ensuring the credibility and reliability of the mediation process, which in turn increases the willingness of parties to engage in mediation and improves the overall outcomes of employment disputes. The research identifies key considerations for the development of a future regulatory framework, including the need to strike a balance between confidentiality and transparency, strengthen the enforceability of mediated agreements, and harmonize the standards for mediator training, accreditation, and ethical guidelines. The research results suggest that the implementation of a regulated system for case reporting, the development of specialized tribunals or procedures for efficient enforcement of mediated agreements, and the establishment of comprehensive national standards for mediator qualifications and continuous professional development would contribute to the overall effectiveness of mediation as a dispute resolution mechanism in both developed and developing country contexts.